2022
DOI: 10.1039/d2bm01230h
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of a cell-derived extracellular matrix for the construction of an osteochondral interlayer

Abstract: Osteochondral defects pose an enormous challenge due to the lack of the effective repair strategy. To tackle this issue, the importance of the calcified cartilage interlayer (CCL) in modulating osteochondral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, sGAGs and collagen contents were retained after decellularization, which demonstrated that the decellularization process did not greatly affect the ECM composition. In fact, besides sGAGs and collagen, 27,32,39 growth factors such as fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) have also been shown to be retained after the decellularization treatment. 27 In this work, the electrospun scaffolds fabricated were composed of nanofibers, mimicking the scale of fibers and fibrils present in the native PDL, which are of nano-to microsized order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sGAGs and collagen contents were retained after decellularization, which demonstrated that the decellularization process did not greatly affect the ECM composition. In fact, besides sGAGs and collagen, 27,32,39 growth factors such as fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) have also been shown to be retained after the decellularization treatment. 27 In this work, the electrospun scaffolds fabricated were composed of nanofibers, mimicking the scale of fibers and fibrils present in the native PDL, which are of nano-to microsized order.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sGAGs and collagen contents were retained after decellularization, which demonstrated that the decellularization process did not greatly affect the ECM composition. In fact, besides sGAGs and collagen, ,, growth factors such as fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) have also been shown to be retained after the decellularization treatment …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sGAGs and collagen contents were retained after decellularization, which demonstrated that the decellularization process did not greatly affect the ECM composition. In fact, besides sGAGs and collagen [26,31,37], other growth factors have also been reported to be retained after decellularization treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…NPCs can synthesize and deposit their own ECM, allowing scaffolds with specific ECM components and ratios to be fabricated by NPCs [16]. Previous studies have demonstrated the inductive role of cell-derived matrix scaffolds in the differentiation of transplanted stem cells [17,18]. Therefore, matrix microspheres produced by simplex NPCs are ideal scaffolds and have promising applications in treating IVD degeneration.…”
Section: Introductionmentioning
confidence: 99%